Interleukins in chronic liver disease: lessons learned from experimental mouse models - Hammerich, Linda (Dove Medical Press, 2014)
Interleukins represent a class of immunomodulatory cytokines, small intercellular signaling proteins, that are critically involved in the regulation of immune responses. They are produced in large amounts by various cell types during inflammatory reactions, and the balance of cytokines determines the outcome of an immune response. Therefore, cytokines are regarded as interesting therapeutic targets for the treatment of patients with liver diseases. Mouse models provide a good tool for in vivo studies on cytokine function, as human and mouse cytokines share many homologies. Sophisticated mouse models either mimicking distinct pathological conditions or targeting cytokines and cytokine-signaling pathways in the liver or even in distinct cellular compartments have provided enormous insight into the different functions of interleukins during hepatic inflammation. Interleukins may have pro- as well as anti-inflammatory functions in chronic liver diseases, some interleukins even both, dependent on the inflammatory stimulus, the producing and the responding cell type. IL-17, for example, promotes hepatic fibrogenesis through activation of hepatic stellate cells and facilitates development of liver cancer through recruitment of myeloid-derived suppressor cells. IL-22, on the other hand, protects from development of fibrosis or steatohepatitis. IL-12 balances T-helper (Th)-1 and Th2 cell responses in infectious disease models. IL-13 and IL-33, two cytokines related to Th2 cells and innate lymphoid cells, promote fibrotic responses in the liver. IL-10 is the prototypic anti-inflammatory interleukin with tissue-protective functions during chronic liver injury and fibrogenesis. Despite its critical role for inducing the acute-phase response in the liver, IL-6 signaling is protective during fibrosis progression, but promotes hepatocellular carcinoma. Experimental studies in mice help to define the exact influence of a specific cytokine on the outcome of chronic liver diseases and to identify useful therapeutic targets.